Evidence of spatial periodic firing in the subiculum of mice - Abad-Perez, P.; Rigamonti, G.; Molina-Paya, F. J.; Cabral-Pereira, G.; Esteve-Campello, Miriam; Scott, R.; Borrell, V.; Martínez-Otero, L.; Falco, A.; Brotons-Mas, J. R. (Frontiers in Neural Circuits, 2025)
The subiculum is a critical node of the hippocampal formation, integrating multiple circuits—including thalamic inputs and afferents from CA1 and medial entorhinal cortex—and projecting broadly to cortical and subcortical targets. Yet its contribution to spatial coding remains incompletely understood. We recorded single-unit activity in freely moving mice using two complementary electrophysiological approaches: (i) chronic tetrodes targeting CA1 and the dorsal subiculum (SUB), and (ii) 64-channel linear silicon probes targeting dorsal SUB. In addition to place cells, boundary-vector cells (BVCs) and corner cells (CCs), we identified a subset of subicular neurons that exhibited spatially periodic, grid-like firing patterns. This phenomenon was replicated across recording technologies, indicating that periodic coding is a consistent feature of the mouse subiculum. Compared with CA1 place cells, SUB spatial neurons exhibited lower spatial information and reduced within-session stability, suggesting distinct coding regimes across hippocampal subregions. Sampling along the proximodistal axis with probe arrays further revealed that burst propensity correlated positively with spatial information at more distal recording sites, consistent with known physiological gradients in subiculum and echoing relationships seen in CA1. Together, these results expand the repertoire of identified spatial codes in SUB and support the view in which subiculum contributes to geometry- and periodicity-based representations that complement CA1 and entorhinal spatial coding, thereby shaping downstream computations in cortico-subcortical circuits.